Systematic Method For Cutting Forces Characterization For XY Milling Table Ballscrew Drive System - Abdullah, Lokman; Jamaludin, Zamberi; Chiew, Tsung Heng; Rafan, Nur Aidawaty (IJENS, 2012)
Inclusion of disturbances in the control system structure of XY table during simulation process is crucial in order to closely replicate the real system in the simulation structure. An example of the distinguished disturbances during cutting operation is cutting forces. It can affect the accuracy of actual position of x and y-axis movement during the cutting operation. Thus, it is important for control designer to include the cutting force disturbance before designing the controller for the XY table system. This paper is focused on the fundamental aspect on how to extract the useful cutting forces data from the raw cutting force data by showing the step by step procedure on how to implement the process. In addition, method on how to convert from the selected cutting forces disturbance data into the form of voltage so that the disturbances is possible to be injected into the system is also being touched and finally, the discussion on the relationship between machine spindle speed and the cutting force generated is also being addressed comprehensively.